2023
DOI: 10.1111/lang.12620
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Sampling Biases, Advancing Inclusivity, and Rethinking Theoretical Accounts in Second Language Acquisition: Introduction to the Special Issue SLA for All?

Aline Godfroid,
Sible Andringa

Abstract: The social sciences have grappled with sampling biases, perhaps most notably the prevalent reliance on convenience samples drawn from university student populations. Researchers in second language acquisition (SLA) have likewise taken steps to assess and address the scope of these biases and their effects on theory construction. This special issue presents a collection of replications and registered replication reports comprising one such initiative, titled SLA for All? The replications aimed to evaluate the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Our science may not provide answers to questions for a vast majority of language learners" (p. 139). As recent initiatives demonstrate (e.g., SLA for All), we know less than we think we do about our phenomena of interest, and sweeping claims from this narrow evidence base about what works and for whom border on scholarly hubris (Godfroid & Andringa, 2023). In light of this unsustainable state of affairs, we should practice greater epistemic humility (Hedges, 2018).…”
Section: Challenge 3: Treatment Fidelity Should Be Balanced With Indi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our science may not provide answers to questions for a vast majority of language learners" (p. 139). As recent initiatives demonstrate (e.g., SLA for All), we know less than we think we do about our phenomena of interest, and sweeping claims from this narrow evidence base about what works and for whom border on scholarly hubris (Godfroid & Andringa, 2023). In light of this unsustainable state of affairs, we should practice greater epistemic humility (Hedges, 2018).…”
Section: Challenge 3: Treatment Fidelity Should Be Balanced With Indi...mentioning
confidence: 99%
“…However, multisite sampling is a strategy that aims to mitigate the "range restriction" that results from narrow sampling, and undercuts attempts to establish generalizable and transferable links between interventions and learning outcomes (Moranski & Zeigler, 2021). That is, our knowledge base is less likely to be confined to explanations of how interventions work with populations of literate, highly educated, affluent language learners in well-resourced classroom settings of the global north (Godfroid & Andringa, 2023). Still, diverse sampling should be based on reciprocal, mutually beneficial engagements and equitable knowledge exchange with underrepresented stakeholders rather than extractive "parachute research" (Gewin, 2023), which perpetuates historic disadvantages through one-off or short-term projects planned, executed, and reported without seeking substantive local expertise or input.…”
Section: Challenge 3: Treatment Fidelity Should Be Balanced With Indi...mentioning
confidence: 99%
“…The remaining 9% of the participants came from 55 additional countries. Compared to many studies in SLA (see Andringa & Godfroid, 2020;Godfroid & Andringa, 2023;Plonsky, 2023), this sample is much more diverse in terms of educational level, target language, and geographic location. Full participant information is provided in Supplementary Material A.…”
Section: Participantsmentioning
confidence: 99%
“…The results of a PCA confirmed that the collective influence of the four UTAUT variables (i.e., performance expectancy, effort expectancy, MALL attitude, social influence) accounted for about 69.9% of the variance, suggesting the applicability of the UTAUT for future studies into profiling learners in technology-enhanced L2 learning contexts. Furthermore, we explored MALL with a focus on a diverse group of adult L2 learners in informal settings, a shift from previous studies that largely centered on university students (Godfroid & Andringa, 2023;Plonsky, 2023). Such contextual differences might influence the extent to which each UTAUT variable could affect L2 learners' intention to use apps.…”
Section: Context-dependent Utaut Variables For Mall Engagementmentioning
confidence: 99%